Removal of Parabens from Aqueous Solution Using β-Cyclodextrin Cross-Linked Polymer - Chin, Yuk Ping; Mohamad, Sharifah; Abas, Mhd Radzi (MDPI, 2010)
The removal of four parabens, methyl-, ethyl-, propyl-, and benzyl-paraben, by β-cyclodextrin (β-CD) polymer from aqueous solution was studied. Different β-CD polymers were prepared by using two cross-linkers, i.e., hexamethylene diisocyanate (HMDI) and toluene-2,6-diisocyanate (TDI), with various molar ratios of cross-linker. β-CD-HMDI polymer with molar ratio of 1:7 and β-CD-TDI polymer with ratio 1:4 gave the highest adsorption of parabens among the β-CD-HMDI and β-CD-TDI series, and were subsequently used for further studies. The adsorption capacity of β-CD-HMDI is 0.0305, 0.0376, 0.1854 and 0.3026 mmol/g for methyl-, ethyl-, propyl-, and benzyl-paraben, respectively. β-CD-TDI have higher adsorption capacities compared with β-CD-HMDI, the adsorption capacity are 0.1019, 0.1286, 0.2551, and 0.3699 mmol/g methyl-, ethyl-, propyl-, and benzyl-paraben respectively. The parameters studied were adsorption capacity, water retention, and reusability. Role of both cross-linker in adsorption, hydrophobicity of polymers, and adsorption capacity of different parabens were compared and discussed. All experiments were conducted in batch adsorption technique. These polymers were applied to real samples and showed positive results.